Untangling neolithic and bronze age mitochondrial lineages in South Asia - Silva, M. (2019)
Two key moments shaped the extant South Asian gene pool within the last 10 thousand years (ka): the Neolithic period, with the advent of agriculture and the rise of the Harappan/Indus Valley Civilisation; and Late Bronze Age events that witnessed the abrupt fall of the Harappan Civilisation and the arrival of Indo-European speakers. This study focuses on the phylogeographic patterns of mitochondrial haplogroups H2 and H13 in the Indian Subcontinent and incorporates evidence from recently released ancient genomes from Central and South Asia. It found signals of Neolithic arrivals from Iran and later movements in the Bronze Age from Central Asia that derived ultimately from the Steppe. This study shows how a detailed mtDNA phylogeographic approach, combining both modern and ancient variation, can provide evidence of population movements, even in a scenario of strong male bias such as in the case of the Bronze Age Steppe dispersals.